(untitled) (ModaPalavra e-periódico, 2016)
With the growth of the search for more comfortable and quality products by users, development and manufacture of garments need to fit this demand, improving its processes. In this sense, the research aims to develop a comparative study of draping and flat pattern as the manufacture of articles on high compression mesh. Considering that the draping is widely used in the development of flat fabric articles while the application mesh is relatively rare, however, a preliminary study have demonstrated the ease of construction with more ergonomic modeling technique. So, to deepen and facilitate this discussion, the research will be divided into two phases, the theoretical first and second applied, which subdividide in three phases: I) preparation of modeling a sporting ladies’ top model in mesh fabric with high compression (suplex) using the two techniques; II) gathering information on the construction of the molds in each technique; III) analysis of the obtained information and preparation of comparative description of the results.